(untitled) (Tikrit Journal of Veterinary Science, 2025)
This study assessed the regenerative potential of a bioactive glass–acacia gum composite for repairing critical-sized radial bone defects in rabbits. Under general anaesthesia, a 10mm segmental defect was created in the distal radius. Over 12 weeks macroscopical examination showed proper implant integration in the treated group, with no signs of infection or rejection, while control animals exhibited persistent fibrous tissue and non-union. Histopathologically, the treated group showed early hyaline cartilage and trabecular bone formation with continued ossification and reduced inflammation due to the acacia gum additive which minimized inflammatory response and controlled bioactive glass degradation. In contrast the control group does not heal spontaneously and remains filled with fibrous connective tissue. These results demonstrate that the BG–acacia composite reflecting both osteoconductive and anti-inflammatory properties of the implant and supports reliable bone regeneration and may serve as a promising implant in critical defect repair.